The Influence of Personal Selling on the Interest in Gold Pawn at Bank Syariah Indonesia Kupang Branch Office Customers - Ananda, Lidea; Nazarudin, Hamzah; Kamuri, Klaasvakumok J. (CV. Jala Berkat Abadi, 2025)
This study aims to explore the influence of promotional activities on customer interest in using the Gold Pawn service at Bank Syariah Indonesia (BSI) Kupang Branch. The main focus is on the effectiveness of promotion strategies, particularly personal selling techniques, which include five elements: sales skills, customer approach, product presentation, handling objections, and encouraging purchasing decisions. Customer interest is measured across four dimensions: transactional, referential, preferential, and exploratory. The research used a quantitative method with a survey of 45 active customers. Data were obtained through questionnaires and analyzed using validity tests, reliability tests, simple linear regression, and t-tests. The results indicated that respondents were predominantly productive-age women with higher education and permanent employment. The average score for personal selling is 4.12, and for mortgage interest, it is 3.87. A strong correlation was found between personal selling and interest in mortgaging (r = 0.734), with a contribution of 52.9%. For every one-point increase in personal selling, interest in mortgaging increased by 0.588 significantly.